Opening address - J.A. Lamprecht (Communicare)
Organisational communication evolves around the forming of relationships between people who strive to achieve a common goal. To be successful, effective communication is a necessity in the modern organisation. Three factors that are closely linked to the effectiveness of organisational communication are discussed. Firstly, internal and external changes in the organisation can have an effect on the communication between management and worker. Secondly, the impact of communication and performance on productivity is highlighted. Thirdly, it was emphasized that the industrial training needs in South Africa demand effective communication